Penggunaan Bahasa Indonesia dan Bahasa Gen Z di Kalangan Remaja pada Lagu Komang Karya Raim Laode - Siti Nur Khotijah; Yulen Lethulur; Sri Utami (Tarbiatuna: Journal of Islamic Education Studies, 2025)
This research aims to analyze the use of Indonesian and Gen Z languages ​​among teenagers in the song "Komang" by Raim Laode. This song was chosen because of its popularity among teenagers and the use of interesting language, namely a mixture of Indonesian and Gen Z languages. The research method used was content analysis with a qualitative approach. Research data in the form of the lyrics of the song "Komang" were analyzed to identify the use of Indonesian and Gen Z languages, as well as the meaning and function of the use of these languages. The research results show that the song "Komang" uses both types of language creatively and effectively. Indonesian is used to convey the main message of the song, namely an expression of love and admiration for someone named Komang. Meanwhile, Gen Z language is used to create a familiar, relaxed and contemporary impression, so that this song is more easily accepted and understood by teenagers. Gen Z's use of language also functions as identity and self-expression for teenagers, as well as strengthening feelings of connection between generations. The conclusion of this research is that the song "Komang" successfully combines Indonesian and Gen Z languages ​​in its lyrics, thus creating a work that is relevant and attractive to teenagers. This song also shows that language can be a bridge between generations, as well as an expression of identity and creativity.